Automated deduction – CADE-25 : 25th International Conference on Automated Deduction, Berlin, Germany, August 1-7, 2015 : proceedings /: 25th International Conference on Automated Deduction, Berlin, Germany, August 1-7, 2015 : proceedings. ([2015]) - Unknown
No abstract available